Agronomic performance of common bean genotypes at Sinop, MT, Brazil - Guilherme, Scheila Roberta; Rodrigues, Cinthia Souza; Botelho, Flávia Barbosa Silva; Zambiazzi, Everton Vinícius; Smiderle, Éder Cristian; Souza, Daiane Cristina Terras (MAGISTRA, 2015)
Abstract: Brazil is the largest bean producer in the world, but the expansion of this crop is still needed. For this, it is necessary the recommendation of specific cultivars for other environments. This study aimed to evaluate breeding lines of common bean in order to recommend to the northern region of Mato Grosso state, Brazil. The experiments were conducted during 2010 and 2011 crop years and thirty two common bean genotypes were tested, including cultivars and breeding lines of the groups Carioca, Jalo, Black and Rajado, with three replications in a randomized block design. Each plot consisted of three rows of two meters in length. The evaluated variables were grain yield (kg.ha-1), plant size, lodging and number of days to flowering. For the carioca group, BRS Requinte resulted in high yield and BRS Cometa in better characteristics related to harvest. Jalo Precoce and BRS Supremo presented the higher yield for the Jalo and Black group, respectively. In the Black group, BRS Supremo was the genotype with higher resistance to lodging. Key words: Phaseolus vulgaris, Breeding programs, Grain yield